Entrepreneurship Learning with Islamic Identity (Case Study at Universitas Nahdlatul Ulama Surabaya) - Zaki Gufron Alfian (PT FORMOSA CENDEKIA GLOBAL, 2024)
Various efforts have been made to develop innovative entrepreneurship learning models. Universitas Nahdlatul Ulama Surabaya (Unusa) claims to have implemented Islamic self-identity entrepreneurship learning. This research aims to uncover the essence of Islamic self-identity entrepreneurship learning and its process. The study utilizes entrepreneurship learning theory and Islamic economic principles to analyze the findings, supported by general learning theory and Islamic entrepreneurship concepts. The research finds that the concept of Islamic self-identity entrepreneurship learning at Unusa fundamentally serves as coursework oriented towards Ilahiyah economics and Islamic economic principles (tauhid, khalifah, and ‘adl). The Islamic self-identity entrepreneurship learning process at Unusa is carried out through five phases: planning, theory delivery, learning practice, business implementation, and ongoing evaluation.